1999
DOI: 10.1097/00000372-199904000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Overexpression in Spitz Nevi: An Immunohistochemical Study

Abstract: The morphologic distinction between Spitz nevus and malignant melanoma can be difficult. Because cyclin D1 has been reported to be overexpressed in malignant melanomas, but not in common acquired nevi, we hypothesized that cyclin D1 might be a useful marker to distinguish Spitz nevi from malignant melanoma. Thus, we assessed for cyclin D1 expression in 11 Spitz nevi (10 compound and 1 intradermal) and 9 malignant melanomas (4 Clark stages I-III and 5 Clark stages IV-V) using an immunohistochemical method and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
45
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 12 publications
7
45
0
Order By: Relevance
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26].…”
Section: Discussionsupporting
confidence: 93%
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26].…”
Section: Discussionsupporting
confidence: 93%
“…16,17,22,41 Nagasaka et al 16 found that all Spitz nevi had a relatively low MIB-1 index (mean 3.2%), which was significantly lower than that of malignant melanoma (mean 15.3%). Similarly, Kanter-Lewensohn et al 17 found an average MIB-1 index of 4% in Spitz nevi and 29.7% in malignant melanoma and Bergman et al 22 reported 1.5% for Spitz nevi vs 14.9% for malignant melanoma.…”
Section: Discussionmentioning
confidence: 98%
“…40 Spitz nevi also display evidence of cell cycle deregulation such as increased cyclin D1, p21, p16, p27, and phospho-ERK expression, which may partly account for the overlapping immunoprofile seen in Spitz nevi and malignant melanoma. 16,36 The adverse biologic effect of p21 and cyclin D1 overexpression in Spitz nevi might be mitigated by other properly functioning G1 regulatory mechanisms still present in Spitz nevi, but lost in malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations